Civic Education in the 21st Century: A Bibliometric Analysis of Scholarly Trends - Sumarwoto, Sumarwoto; Handitya, Binov; Soeharto, Soeharto (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study was to analyze the evolving landscape of civic education in the 21st century through a comprehensive bibliometric analysis of scholarly trends. VOSviewer was utilized for its ability to effectively visualize data in the form of maps. The analysis focuses on two key aspects: trends in research based on keywords, titles, and abstracts, and the geographical distribution of research activity across countries. The results highlight the top five countries leading in civic education research: the United States, the United Kingdom, Germany, Australia, and Spain, with Indonesia ranked 32nd. The findings emphasize the need for continued development in civic education policies and practices globally, particularly addressing disparities in lower-ranked countries. This study contributes to understanding how civic education can be effectively implemented and researched, offering insights for policymakers and educators to strengthen civic education systems worldwide. The practical implications of these findings suggest that policymakers and educators can leverage these insights to design civic education programs that are both contextually relevant and capable of bridging existing educational gaps.